Blended learning for teacher training: benefits, challenges, and recommendations (Educational Dimension, 2023)
This study examines how blended learning (BL) was used for teacher training and retraining during and after the COVID-19 pandemic, based on a systematic analysis of 27 scientific sources from the Scopus database. BL is a flexible and personalized mode of learning that combines face-to-face, synchronous, and asynchronous distance learning methods, as well as various ICT tools and pedagogical technologies. The study identifies the main approaches, benefits, and challenges of BL implementation in teacher education. It reveals that BL can enhance teachers’ access to resources, communication, interaction, collaboration, reflection, and creativity. However, it also requires reliable technology, technical support, and adequate training for both teachers and students.